La-Ce mixed rare earth high-strength high-conductivity aluminum rare earth alloy and preparation method thereof
Patent Information
- Application Number
- CN202611095666.9
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2026-07-22
- Publication Date
- 2026-10-09
AI Technical Summary
[0007]第四,现有轻稀土铝合金的性能仍有提升空间
[0066]与现有技术相比,本发明具有以下显著优势:
Smart Images

Figure CN122879568A_ABST
Abstract
Description
Technical Field
[0001] This invention belongs to the field of non-ferrous metal material processing technology, specifically relating to a high-strength, high-conductivity aluminum rare earth alloy that uses high-abundance, low-cost La-Ce mixed rare earth elements to replace some heavy rare earth elements and its preparation method, which can be applied to fields such as power transmission, new energy vehicles, and electrical equipment. Background Technology
[0002] With the deepening of the "aluminum-for-copper" strategy, high-strength and high-conductivity aluminum alloy materials are increasingly widely used in power transmission and new energy vehicles. Rare earth elements, as important microalloying elements in aluminum alloys, can effectively refine grains, purify the melt, improve the uniformity of microstructure, and significantly enhance the overall performance of aluminum alloys.
[0003] However, existing rare earth aluminum alloy technologies mainly have the following problems:
[0004] First, the high dependence on heavy rare earth elements leads to persistently high costs. Existing high-performance rare earth aluminum alloys largely rely on heavy rare earth elements such as erbium (Er) and ytterbium (Yb), whose prices are 5 to 10 times higher than light rare earth elements (such as lanthanum (La) and cerium (Ce)). Chinese invention patent publication number CN120158658A discloses a rare earth aluminum alloy cable material containing 0.3–0.6 wt% Er and 0.1–0.3 wt% Yb; another Chinese invention patent publication number CN119812788A discloses related rare earth aluminum alloy technology. The extensive use of heavy rare earth elements has significantly increased the cost of aluminum alloy materials.
[0005] Secondly, the effect of a single rare earth element is limited, and there is an optimal addition window. Studies have shown that the strengthening effect of a single rare earth element (such as adding Ce or La alone) on aluminum alloys is limited, and there is an optimal addition window (typically 0.1–0.5%). Beyond this window, excessive rare earth elements will form coarse, brittle intermetallic compound phases (such as Al). 11 Brittle phases such as RE3 and Al4RE can become crack initiators under stress, severely impairing the material's plasticity and toughness. Adding 0.15% lanthanum and cerium mixed rare earth elements yields aluminum alloys with optimal overall performance.
[0006] Third, the La-Ce mixed rare earth elements exhibit a significant synergistic effect. Studies have shown that La and Ce have a synergistic effect in aluminum alloys. La is mainly enriched at grain boundaries, playing a role in purifying grain boundaries and improving thermal stability; while Ce is mainly dispersed within the grains in the form of Al3Ce, playing a role in refining grains and precipitation strengthening. By rationally proportioning La and Ce, the maximum strengthening effect can be achieved under conditions of relatively low total addition.
[0007] Fourth, there is still room for improvement in the performance of existing light rare earth aluminum alloys. Currently, the highest conductivity of La-Ce mixed rare earth aluminum alloys is approximately 60.9% IACS, and the tensile strength is approximately 176.1 MPa. How to effectively reduce the cost of rare earth raw materials while ensuring high strength and high conductivity, and develop low-cost aluminum-rare earth alloys suitable for power transmission and new energy vehicles, remains a pressing problem to be solved in this field.
[0008] Therefore, how to effectively reduce the cost of rare earth raw materials while ensuring high conductivity and high strength, and develop low-cost aluminum-rare earth alloys suitable for power transmission and new energy vehicles, remains a pressing problem to be solved in this field. Summary of the Invention
[0009] (I) Purpose of the Invention
[0010] The purpose of this invention is to overcome the shortcomings of existing technologies and provide a La-Ce mixed rare earth high-strength and high-conductivity aluminum rare earth alloy and its preparation method. This alloy uses high-abundance, low-cost La-Ce mixed rare earth elements to partially replace heavy rare earth elements, achieving grain refinement and microstructure optimization through the synergistic effect between rare earth elements, thereby significantly reducing raw material costs while maintaining high strength and high conductivity.
[0011] (II) Technical Solution
[0012] 1.Alloy composition
[0013] A La-Ce mixed rare earth high-strength and high-conductivity aluminum rare earth alloy, characterized in that it is composed of the following components by mass percentage:
[0014] Mixed rare earth elements (RE): 0.10–0.35%
[0015] Zirconium (Zr): 0.10–0.18%
[0016] Iron (Fe): 0.10–0.15%
[0017] Copper (Cu): 0.10–0.30%
[0018] Magnesium (Mg): 0.10–0.30%
[0019] Silicon (Si): 0.10–0.30%
[0020] The balance is aluminum (Al) and unavoidable impurities.
[0021] Furthermore, the mixed rare earth (RE) is a mixture of lanthanum (La) and cerium (Ce), wherein the mass ratio of La to Ce is 1:2 to 1:4.
[0022] Preferably, the mass ratio of La to Ce is 1:2.
[0023] Furthermore, the preferred mass percentage of each component in the alloy is:
[0024] Mixed rare earth elements (RE): 0.15–0.30%
[0025] Zirconium (Zr): 0.12–0.16%
[0026] Iron (Fe): 0.11–0.14%
[0027] Copper (Cu): 0.15–0.25%
[0028] Magnesium (Mg): 0.15–0.25%
[0029] Silicon (Si): 0.15–0.25%
[0030] The balance is aluminum (Al) and unavoidable impurities.
[0031] Furthermore, the total mass percentage of the unavoidable impurities does not exceed 0.15%, and the percentage of a single impurity element does not exceed 0.05%.
[0032] 2. Microstructural characteristics
[0033] The microstructure of the alloy has the following characteristics:
[0034] Furthermore, the microstructure of the alloy contains the following strengthening phases:
[0035] Nanoscale precipitates with a core-shell structure: formed by a mixture of rare earth elements La, Ce and Zr, containing a rare earth-rich (La / Ce) core and a zirconium-rich (Zr) shell. This core-shell structure has the dual effect of pinning grain boundaries to inhibit recrystallization and precipitation strengthening, which significantly improves the thermal stability of the alloy.
[0036] Mg2Si strengthening phase: formed by Mg and Si elements, it provides age-hardening effect to the alloy;
[0037] Al 13 Fe4 dispersed phase: formed by Fe element, which helps to refine the as-cast grains.
[0038] Preferably, the average grain size of the alloy is ≤50μm, and the overall average size of the core-shell structured nanoprecipitates is ≤30nm (the thickness of the zirconium-rich shell is 5-10nm).
[0039] 3. Preparation method
[0040] A method for preparing the above-mentioned La-Ce mixed rare earth high-strength and high-conductivity aluminum rare earth alloy, characterized by comprising the following steps:
[0041] Step 1, Ingredient preparation: Prepare raw materials according to the stated ingredient ratio. The purity of the pure Al used is ≥99.85%, and the purity of the intermediate alloy is ≥99.5%.
[0042] Step 2, Melting: Add the raw materials to the melting furnace and heat them to 720-760°C under a protective atmosphere for melting. After the raw materials are completely melted, keep them at that temperature for 15-30 minutes.
[0043] Step 3, Refining: The melt is refined using a combination of argon and refining agent. The degassing time is 15-20 minutes and the refining temperature is 710-740℃.
[0044] Preferably, the refining agent is a mixture of NaF and NaCl in a weight ratio of 1:1, and the amount added is 0.1-0.2% of the melt weight;
[0045] Step 4, Casting: The refined melt is semi-continuously or continuously cast at 680-710℃ to obtain ingots;
[0046] Step 5, Homogenization treatment: Homogenize the ingot by heating it to 530-550℃ and holding it for 8-12 hours. After removing it from the furnace, quench it in water or air cool it.
[0047] Preferably, the homogenization process is a single-stage homogenization process, which involves heating to 540°C and holding for 10 hours.
[0048] Step 6, hot deformation processing: The homogenized ingot is heated to 450-500℃ for hot extrusion or hot rolling, with an extrusion ratio of (10-30):1, to produce wire rods or profiles;
[0049] Step 7, Solution treatment: The hot-deformed wire blank is subjected to solution treatment by heating to 520-550℃ and holding for 1-3 hours, followed by water quenching to room temperature;
[0050] Step 8, Aging treatment: The solution-treated material is subjected to aging treatment by heating to 160-200℃ and holding for 8-16 hours, followed by air cooling;
[0051] Preferably, the aging treatment is a single-stage aging process, involving heating to 175°C and holding for 10 hours;
[0052] Step 9, Cold working (optional): The aged material is cold drawn or cold rolled to obtain conductors or profiles of the required specifications.
[0053] 4. Principles of Ingredient Design
[0054] The composition design of this invention follows the following principles:
[0055] (1) Selection criteria for La-Ce mixed rare earth elements
[0056] Studies have shown that La and Ce have a synergistic effect in aluminum alloys. La is mainly enriched at grain boundaries, playing a role in purifying grain boundaries and improving thermal stability. Ce and La together form a rare earth-rich core of a core-shell structured nanoprecipitate, which refines the grains and provides precipitation strengthening through a dispersed distribution. By controlling the La:Ce ratio to 1:2 to 1:4, the complementary functions of La and Ce can be achieved, maximizing the strengthening effect under conditions of relatively low total addition (0.10–0.35%).
[0057] (2) Synergistic effect of each element
[0058] Mg and Si: form the Mg2Si strengthening phase, which provides significant age-hardening effect to the alloy;
[0059] Cu: a solid solution strengthening element that can improve the strength and heat resistance of alloys;
[0060] Zr: Together with La and Ce, it forms a zirconium-rich shell of core-shell nanoprecipitates, which has high thermal stability and can pin grain boundaries and inhibit recrystallization;
[0061] Fe: Forms Al 13 Fe4 dispersed phase helps to refine grains;
[0062] La-Ce mixed rare earth elements: purify the melt, refine the grains, and improve the uniformity of the microstructure.
[0063] (3) Cost control strategy
[0064] Replacing heavy rare earth elements such as Er and Yb with La-Ce mixed rare earth elements reduces the cost of rare earth raw materials by 50-70%. Simultaneously, by optimizing the heat treatment process (single-stage homogenization + single-stage aging), the process energy consumption is reduced by 10-15% compared to two-stage homogenization.
[0065] (III) Beneficial Effects
[0066] Compared with the prior art, the present invention has the following significant advantages:
[0067] 1. Significant cost advantage: By using high-abundance, low-cost La-Ce mixed rare earth elements to replace heavy rare earth elements such as Er and Yb, the cost of rare earth raw materials is reduced by 50-70%. The overall production cost is 20-30% lower than that of similar aluminum alloy products containing heavy rare earth elements.
[0068] 2. Excellent overall performance: The alloy of this invention has a tensile strength ≥176MPa, conductivity ≥60.9%IACS, elongation ≥15%, and strength retention rate at 300℃ ≥85%. Its overall performance reaches or exceeds the level of existing aluminum alloy products containing heavy rare earth elements.
[0069] 3. Rational utilization of rare earth resources: La and Ce are abundant rare earth elements in my country, with rich reserves and stable prices. Replacing scarce heavy rare earth elements with La-Ce mixed rare earth elements is in line with the national strategy for comprehensive utilization of rare earth resources.
[0070] 4. Good process adaptability: The present invention adopts a single-stage homogenization and single-stage aging process, which reduces energy consumption by 10-15% compared with the two-stage homogenization process, improves production efficiency, and facilitates industrial production.
[0071] 5. Broad application prospects: The alloy of this invention is applicable to fields such as power transmission cables, new energy vehicle wiring harnesses, and electrical equipment conductors. Attached Figure Description
[0072] Figure 1 This is a transmission electron microscope image of a rare-earth aluminum alloy monofilament from Example 1 of the present invention, showing the core-shell structured nano-precipitates and Al. 13 Fe4 dispersed phase. In the diagram: 1-Rare earth-rich core; 2-Zirconium-rich outer shell; 3-Al 13 Fe4 dispersed phase; 4-Al matrix. Scale bar is 50 nm.
[0073] Figure 2 This is a comparison chart of the conductivity and tensile strength of Example 1 and Comparative Example 1 (Er-containing heavy rare earth aluminum alloy) of the present invention.
[0074] Figure 3 This is a comparison chart of the heat resistance of Example 1 and Comparative Example 2 (without rare earth aluminum alloy) of the present invention (strength retention rate at 300℃ / 1h). Detailed Implementation
[0075] To make the objectives, technical solutions, and advantages of this invention clearer, the technical solutions of this invention will be described in further detail below with reference to the accompanying drawings and embodiments. However, the following embodiments are only used to explain this invention and do not constitute a limitation on the scope of protection of this invention.
[0076] Test method description:
[0077] The performance tests of the embodiments and comparative examples of this invention were all conducted in accordance with the following standards:
[0078] Tensile strength: Tested according to GB / T 228.1-2021 "Metallic materials, tensile testing - Part 1: Test method at room temperature";
[0079] Conductivity: Tested according to GB / T 351-2019 "Methods for Measurement of Resistivity of Metallic Materials";
[0080] Elongation: Tested according to GB / T 228.1-2021;
[0081] Heat resistance (residual strength at 300℃ / 1h): tested according to GB / T 20957.1-2007 "High Temperature Tensile Test Method";
[0082] Grain size: Tested according to GB / T 6394-2017 "Method for determination of average grain size of metals".
[0083] Raw material description:
[0084] The purity of the raw materials used in the embodiments of the present invention is as follows:
[0085] Pure Al: purity ≥ 99.85%;
[0086] Pure Mg: Purity ≥ 99.9%;
[0087] Al-20%Cu, Al-20%Si, Al-10%Zr, Al-10%Fe, Al-5%La, and Al-5%Ce master alloys: all with a purity ≥99.5%.
[0088] Impurity control instructions:
[0089] In this embodiment of the invention, the total mass percentage of unavoidable impurities does not exceed 0.15%, and the percentage of a single impurity element does not exceed 0.05%.
[0090] Core-shell structure characterization methods:
[0091] In this embodiment of the invention, the microstructure and elemental distribution of the core-shell structured nanoprecipitates were characterized using transmission electron microscopy (TEM) combined with energy dispersive X-ray spectroscopy (EDS), in accordance with GB / T 47182-2026 "Microbeam analysis and analytical electron microscopy for measuring the shell wall thickness of core-shell particles".
[0092] Example 1 (La:Ce = 1:2, optimal ratio)
[0093] 1. Ingredients
[0094] The ingredients are prepared according to the final composition of RE (La:Ce = 1:2) 0.25%, Zr 0.15%, Fe 0.12%, Cu 0.20%, Mg 0.20%, Si 0.20%, with the balance being Al.
[0095] The content of La was 0.083%, and the content of Ce was 0.167% (La:Ce = 1:2).
[0096] Other elements: Zr 0.15%, Fe 0.12%, Cu 0.20%, Mg 0.20%, Si 0.20%.
[0097] 2. Smelting
[0098] Pure Al, Al-20% Cu, Al-20% Si, Al-10% Zr, Al-10% Fe, Al-5% La, Al-5% Ce master alloy and pure Mg are added to a melting furnace in the specified proportions and heated to 740°C under argon protection for melting. After the raw materials are completely melted, the furnace is held at that temperature for 20 minutes.
[0099] 3. Refining
[0100] The melt was refined using a combination of argon gas and a refining agent. The refining agent was a mixture of NaF and NaCl in a weight ratio of 1:1, and the amount added was 0.15% of the melt weight. The degassing time was 15 minutes, and the refining temperature was 730℃.
[0101] 4. Casting
[0102] The refined melt is semi-continuously cast at 700°C to obtain ingots.
[0103] 5. Homogenization treatment
[0104] The ingots are heated to 540℃ and held for 10 hours for homogenization, and then water-quenched after being taken out of the furnace.
[0105] 6. Hot extrusion
[0106] The homogenized ingot is heated to 480℃ and hot extruded at an extrusion ratio of 20:1 to produce... Wire rod blank.
[0107] 7. Solution treatment
[0108] The hot-extruded wire rod was heated to 530℃ and held for 2.0 hours, then water-quenched to room temperature.
[0109] 8. Timeliness processing
[0110] The solution-treated wire rod was heated to 175°C and held for 10 hours for aging treatment, followed by air cooling.
[0111] 9. Performance Testing
[0112] The properties of the resulting alloy material were tested and are as follows:
[0113] Tensile strength: 183MPa
[0114] Conductivity: 61.5% IACS
[0115] Elongation: 18.5%
[0116] Strength retention rate at 300℃ for 1 hour: 87.5%
[0117] Average grain size: 45μm
[0118] 10. Cost Analysis
[0119] The rare earth raw material cost of the alloy in this embodiment is about 30% of that of Er-containing heavy rare earth aluminum alloys, and the overall production cost is reduced by about 25% compared with similar products containing heavy rare earths.
[0120] Example 2 (La:Ce = 1:3)
[0121] 1. Ingredients
[0122] The ingredients are prepared according to the final composition of RE (La:Ce = 1:3) 0.30%, Zr 0.16%, Fe 0.13%, Cu 0.25%, Mg 0.25%, Si 0.25%, with the balance being Al.
[0123] The content of La is 0.075%, and the content of Ce is 0.225% (La:Ce = 1:3).
[0124] Other elements: Zr 0.16%, Fe 0.13%, Cu 0.25%, Mg 0.25%, Si 0.25%.
[0125] 2. Melting and casting
[0126] Same as Example 1.
[0127] 3. Homogenization treatment
[0128] The ingots are heated to 545℃ and held for 9 hours for homogenization, and then water-quenched after being taken out of the furnace.
[0129] 4. Hot extrusion
[0130] Same as Example 1.
[0131] 5. Solution treatment and aging
[0132] Solution treatment: 535℃ for 2.0 hours; Aging treatment: 180℃ for 12 hours.
[0133] 6. Performance Testing
[0134] The properties of the resulting alloy material were tested and are as follows:
[0135] Tensile strength: 181 MPa
[0136] Conductivity: 61.2% IACS
[0137] Elongation: 17.8%
[0138] Strength retention rate at 300℃ for 1 hour: 86.5%
[0139] Example 3 (Low Rare Earth Content)
[0140] 1. Ingredients
[0141] The ingredients are prepared according to the following final composition: RE (La:Ce = 1:2) 0.15%, Zr 0.12%, Fe 0.11%, Cu 0.15%, Mg 0.15%, Si 0.15%, with the balance being Al.
[0142] The content of La is 0.05%, and the content of Ce is 0.10% (La:Ce = 1:2).
[0143] Other elements: Zr 0.12%, Fe 0.11%, Cu 0.15%, Mg 0.15%, Si 0.15%.
[0144] 2. Melting and casting
[0145] Same as Example 1.
[0146] 3. Homogenization treatment
[0147] The ingots are heated to 535℃ and held for 8 hours for homogenization, and then water-quenched after being taken out of the furnace.
[0148] 4. Hot extrusion
[0149] Same as Example 1.
[0150] 5. Solution treatment and aging
[0151] Solution treatment: hold at 525℃ for 1.5 hours; Aging treatment: hold at 170℃ for 8 hours.
[0152] 6. Performance Testing
[0153] The properties of the resulting alloy material were tested and are as follows:
[0154] Tensile strength: 175MPa
[0155] Conductivity: 62.0% IACS
[0156] Elongation: 19.2%
[0157] Strength retention rate at 300℃ for 1 hour: 85.0%
[0158] 7. Cost Analysis
[0159] In this embodiment, the amount of rare earth used is the lowest, and the cost of rare earth raw materials is about 20% of that of aluminum alloys containing heavy rare earths, resulting in the lowest overall production cost.
[0160] Example 4 (High Rare Earth Content)
[0161] 1. Ingredients
[0162] The ingredients are prepared according to the final composition of RE (La:Ce = 1:2) 0.35%, Zr 0.18%, Fe 0.14%, Cu 0.30%, Mg 0.30%, Si 0.30%, with the balance being Al.
[0163] The content of La was 0.117%, and the content of Ce was 0.233% (La:Ce = 1:2).
[0164] 2. Melting and casting
[0165] Same as Example 1.
[0166] 3. Homogenization treatment
[0167] The ingots are heated to 550℃ and held for 12 hours for homogenization, and then water-quenched after being taken out of the furnace.
[0168] 4. Hot extrusion
[0169] Same as Example 1.
[0170] 5. Solution treatment and aging
[0171] Solution treatment: hold at 545℃ for 2.5 hours; Aging treatment: hold at 185℃ for 14 hours.
[0172] 6. Performance Testing
[0173] The properties of the resulting alloy material were tested and are as follows:
[0174] Tensile strength: 185MPa
[0175] Conductivity: 60.8% IACS
[0176] Elongation: 16.5%
[0177] Strength retention rate at 300℃ for 1 hour: 88.0%
[0178] Comparative Example 1 (Er-containing heavy rare earth aluminum alloy)
[0179] Referring to existing Er-containing heavy rare earth aluminum alloy schemes, the alloy was prepared according to the following formula: Er 0.15%, Yb 0.10%, Zr 0.15%, Fe 0.12%, with the balance being Al. The alloy properties were tested and are as follows:
[0180] Tensile strength: 182MPa
[0181] Conductivity: 61.8% IACS
[0182] Elongation: 22.5%
[0183] Strength retention rate at 300℃ for 1 hour: 92.0%
[0184] The cost of rare earth raw materials is approximately 3.5 times that of Example 1.
[0185] Comparative Example 2 (Aluminum alloy without rare earth elements)
[0186] Referring to the standard AA-8000 series aluminum alloy formula, the alloy was prepared using conventional processes with the following composition: Fe 0.60%, Cu 0.20%, Mg 0.08%, Si 0.10%, and the balance Al. The resulting alloy exhibits the following properties after testing:
[0187] Tensile strength: 120MPa
[0188] Conductivity: 59.0% IACS
[0189] Elongation: 15.0%
[0190] Strength retention rate at 300℃ for 1 hour: 70.0%
[0191] Summary of Performance of Examples and Comparative Examples
[0192]
[0193] Conclusion: The La-Ce mixed rare earth aluminum alloys of the present invention (Examples 1-4) are comparable to Comparative Example 1 containing heavy rare earth elements in terms of tensile strength and electrical conductivity. While their elongation and heat resistance are slightly lower, they still meet the requirements for power transmission and electrical equipment applications. Furthermore, the cost of rare earth raw materials is only 20-40% of that of Comparative Example 1, demonstrating a significant overall cost-performance advantage. Compared to Comparative Example 2 without rare earth elements, the tensile strength is increased by more than 40%, the electrical conductivity is increased by 2-3 percentage points, and the heat resistance is significantly improved.
[0194] The above description is merely a preferred embodiment of the present invention and is not intended to limit the scope of protection of the present invention. Any modifications, equivalent substitutions, improvements, etc., made within the spirit and principles of the present invention should be included within the scope of protection of the present invention.
Claims
1. A La-Ce mixed rare earth high-strength and high-conductivity aluminum rare earth alloy, characterized in that, It consists of the following components by weight percentage: Mixed rare earth elements (RE): 0.10–0.35%; Zirconium (Zr): 0.10–0.18%; Iron (Fe): 0.10–0.15%; Copper (Cu): 0.10–0.30%; Magnesium (Mg): 0.10–0.30%; Silicon (Si): 0.10–0.30%; The balance consists of aluminum (Al) and unavoidable impurities; The mixed rare earth (RE) is a mixture of lanthanum (La) and cerium (Ce), with a mass ratio of La to Ce of 1:2 to 1:
4.
2. The La-Ce mixed rare earth high-strength and high-conductivity aluminum rare earth alloy according to claim 1, characterized in that, The mass ratio of La to Ce is 1:
2.
3. The La-Ce mixed rare earth high-strength and high-conductivity aluminum rare earth alloy according to claim 1, characterized in that, It consists of the following components by weight percentage: Mixed rare earth elements (RE) 0.15–0.30%; Zr:0.12~0.16%; Fe: 0.11–0.14%; Cu: 0.15–0.25%; Mg: 0.15–0.25%; Si: 0.15–0.25%; The balance consists of Al and unavoidable impurities.
4. The La-Ce mixed rare earth high-strength and high-conductivity aluminum rare earth alloy according to claim 3, characterized in that, The total mass percentage of the unavoidable impurities does not exceed 0.15%, and the percentage of a single impurity element does not exceed 0.05%.
5. The La-Ce mixed rare earth high-strength and high-conductivity aluminum rare earth alloy according to claim 1, characterized in that, The microstructure of the alloy contains a core-shell structure of nanoprecipitates, Mg2Si reinforcing phases, and Al. 13 Fe4 dispersed phase; the core-shell structured nanoprecipitates contain a rare earth-rich core and a zirconium-rich shell.
6. The La-Ce mixed rare earth high-strength and high-conductivity aluminum rare earth alloy according to claim 1, characterized in that, The alloy has a tensile strength ≥176MPa, electrical conductivity ≥60.9%IACS, elongation ≥15%, and strength retention rate at 300℃ / 1h ≥85%.
7. The La-Ce mixed rare earth high-strength and high-conductivity aluminum rare earth alloy according to claim 1, characterized in that, The average grain size of the alloy is ≤50μm.
8. A method for preparing a La-Ce mixed rare earth high-strength, high-conductivity aluminum rare earth alloy as described in any one of claims 1 to 7, characterized in that, Includes the following steps: Step 1, Ingredient Preparation: Prepare the raw materials according to the stated ingredient ratio; Step 2, Melting: Add the raw materials to the melting furnace and heat them to 720-760°C under a protective atmosphere for melting. After the raw materials are completely melted, keep them at that temperature for 15-30 minutes. Step 3, Refining: The melt is refined using a combination of argon and refining agent. The degassing time is 15-20 minutes and the refining temperature is 710-740℃. Step 4, Casting: The refined melt is cast at 680-710℃ to obtain an ingot; Step 5, Homogenization treatment: Heat the ingot to 530-550℃ and hold for 8-12 hours for homogenization treatment; Step 6, hot deformation processing: The homogenized ingot is heated to 450-500℃ for hot extrusion or hot rolling to produce wire rods or profiles; Step 7, Solution treatment: Heat the hot-deformed wire blank to 520-550℃ and hold for 1-3 hours, then quench it in water to room temperature; Step 8, Aging treatment: Heat the solution-treated material to 160-200℃ and hold for 8-16 hours for aging treatment, then air cool.
9. The preparation method according to claim 8, characterized in that, The refining agent mentioned in step 3 is a mixture of NaF and NaCl in a weight ratio of 1:1, and the amount added is 0.1 to 0.2% of the melt weight.
10. The preparation method according to claim 8, characterized in that, The homogenization process in step 5 is carried out at a temperature of 540°C for 10 hours.
11. The preparation method according to claim 8, characterized in that, The extrusion ratio of the hot extrusion in step 6 is (10-30):
1.
12. The preparation method according to claim 8, characterized in that, The solution treatment in step 7 is performed at a temperature of 530°C for 2 hours.
13. The preparation method according to claim 8, characterized in that, The aging treatment in step 8 is performed at a temperature of 175°C for 10 hours.
Citation Information
Patent Citations
Rare earth aluminum alloy cable joint manufacturing method
CN119812788A
Rare earth aluminum alloy cable material, preparation method and application of rare earth aluminum alloy cable material to power transmission line
CN120158658A